Peptide-Loaded Solid Lipid Nanoparticles Prepared through Coacervation Technique - Marina Gallarate; Luigi Battaglia; E. Peira; Michele Trotta (International Journal of Chemical Engineering)
Stearic acid solid lipid nanoparticles were prepared according to a new technique, called coacervation. The main goal of this experimental work was the entrapment of peptide drugs into SLN, which is a difficult task, since their chemical characteristics (molecular weight, hydrophilicity, and stability) hamper peptide-containing formulations. Insulin and leuprolide, chosen as model peptide drugs, were encapsulated within nanoparticles after hydrophobic ion pairing with anionic surfactants. Peptide integrity was maintained after encapsulation, and nanoparticles can act in vitro as a sustained release system for peptide.